Accuracy of thyroid imaging reporting and data system category 4 or 5 for diagnosing malignancy: a systematic review and meta-analysis - Kim, Dong Hwan; Chung, Sae Rom; Choi, Sang Hyun; Kim, Kyung Won (European radiology, 2020)
Objectives To determine the accuracies of the American College of Radiology (ACR)–thyroid imaging reporting and data systems (TIRADS), Korean (K)-TIRADS, and European (EU)-TIRADS for diagnosing malignancy in thyroid nodules. Methods Original studies reporting the diagnostic accuracy of TIRADS for determining malignancy on ultrasound were identified in MEDLINE and EMBASE up to June 23, 2019. The meta-analytic summary sensitivity and specificity were obtained for TIRADS category 5 (TR-5) and category 4 or 5 (TR-4/5), using a bivariate random effects model. To explore study heterogeneity, meta-regression analyses were performed. Results Of the 34 eligible articles (37,585 nodules), 25 used ACR-TIRADS, 12 used K-TIRADS, and seven used EU-TIRADS. For TR-5, the meta-analytic sensitivity was highest for EU-TIRADS (78% [95% confidence interval, 64–88%]), followed by ACR-TIRADS (70% [61–79%]) and K-TIRADS (64% [58–70%]), although the differences were not significant. K-TIRADS showed the highest meta-analytic specificity (93% [91–95%]), which was similar to ACR-TIRADS (89% [85–92%]) and EU-TIRADS (89% [77–95%]). For TR-4/5, all three TIRADS systems had sensitivities higher than 90%. K-TIRADS had the highest specificity (61% [50–72%]), followed by ACR-TIRADS (49% [43–56%]) and EU-TIRADS (48% [35–62%]), although the differences were not significant. Considerable threshold effects were noted with ACR- and K-TIRADS ( p ≤ 0.01), with subject enrollment, country of origin, experience level of reviewer, number of patients, and clarity of blinding in review being the main causes of heterogeneity ( p ≤ 0.05). Conclusions There was no significant difference among these three international TIRADS, but the trend toward higher sensitivity with EU-TIRADS and higher specificity with K-TIRADS. Key Points • For TIRADS category 5, the meta-analytic sensitivity was highest for the EU-TIRADS, followed by the ACR-TIRADS and the K-TIRADS, although the differences were not significant. • For TIRADS category 5, K-TIRADS showed the highest meta-analytic specificity, which was similar to ACR-TIRADS and EU-TIRADS. • Considerable threshold effects were noted with ACR- and K-TIRADS, with subject enrollment, country of origin, experience level of reviewer, number of patients, and clarity of blinding in review being the main causes of heterogeneity.